TCM therapies combined with chemotherapy for preventing recurrence and metastasis in postoperative II to IIIA NSCLC: A protocol for a systematic review and meta-analysis. Issue 9 (March 2019) - Chen, Shuntai; Zhang, Zhenhua; Zhang, Xiwen; Qi, Runzhi; Jiang, Juling; Zhang, Xing; Xi, Yupeng; Liu, Rui; Guo, Qiujun; Zheng, Honggang; Hua, Baojin
Abstract: Background: Traditional Chinese Medicine (TCM) therapies have been combined with chemotherapy for preventing Recurrence and metastasis in postoperative II to IIIA non-small-cell lung cancer (NSCLC) and the associated better disease-free survival (DFS), but its effects remain elusive. The purpose of this review is to assess the efficacy of TCM therapies as a treatment for postoperative II to IIIA NSCLC. Methods and analysis: Seventh databases will be searched for relevant studies from inception to the present date. We will include randomized controlled trials assessing TCM therapies combined with chemotherapy for preventing Recurrence and metastasis in postoperative II to IIIA NSCLC. The methodological qualities, including the risk of bias, will be evaluated using the Cochrane risk of bias assessment tool, while confidence in the cumulative evidence will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Ethics and dissemination: Ethical approval is not required, as this study is based on the review of published research. This review will be published in a peer-reviewed journal and disseminated both electronically and in print. PROSPERO registration number: The protocol for this systematic review has been registered on PROSPERO under the number CRD42019116594.